HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEARIFAN LOKAL KONSERVASI KUPU-KUPU DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG KABUPATEN MAROS - Dinda Marzuki; Firdaus Daud; Andi Asmawati Azis (UNIVERSITAS NEGERI MAKASSAR, 2023)
This research is Ex Post Facto research which aims to determine the relationship knowledge and attitudes with the local wisdom of community butterfly conservation in the Park Bantimurung Bulusarauang National Maros Regency. Sample in this research as many as 45 people who are limited to three community groups namely; businessmen trade of butterflies, hunters and craftsmen of preservation of butterflies. Research instrument The instruments used were knowledge test instruments, attitude questionnaires and local wisdom questionnaires. The data obtained in this study were analyzed using SPSS version 25.0 for windows. Based on hypothesis testing, the research results show that there is significant relationship between knowledge and attitudes with conservation local wisdom community butterflies in the Bantimurung National Park area.